Identification of Pesticide-Saturated Soil Using Near-Surface Geophysics Method - Putri, Bilqis Aulia; Putri, Amira Sasanti Nugroho; Prameswary, Cevilla Amalia; Ekklesia, Epiphani; Donita, Fataya Tasya; Rahmawati, Nabilah; Agustine, Eleonora; Susilawati, Anggie (Phi: Jurnal Pendidikan Fisika dan Terapan, 2024)
Harmful substances deposited in the soil can disrupt soil functions, leading to environmental pollution and harm. Pesticides are one example of these harmful substances. Absorption of pesticides into the soil can lead to infertility and negatively impact overall soil health. Therefore, a study was conducted to identify pesticide-saturated soil near the surface and map the soil health conditions around Situ Cisanti. The research utilized geoelectric methods and collected soil and water samples from the inlet (a) and outlet (b) areas of Situ Cisanti. After conducting measurements around Situ Cisanti, the data collected include soil resistivity, ranging from 0.483 to 2.04 Ωm (a) and 658 to 2787 Ωm (b). Soil pH levels were 8.9 - 9.0 (a) and 8.9 (b). Soil Electrical Conductivity (EC) and Total Dissolved Solids (TDS) measured 250 - 280 μs and 194 - 207 ppm (a), and 240 μs and 178 ppm (b). Water pH was 7.7 (a) and 8.7 - 9.1 (b). Water EC and TDS were 100 μs and 83 ppm (a), and 80 - 180 μs and 65 - 94 ppm (b). The results indicated higher pesticide contamination in the outlet compared to the inlet, signifying potential risks to soil health.